Hydrogeological Characterization Of Crystalline Bedrock Using Borehole Magnetic Resonance At A Mining Development Site, Northern Finland - Eeva, Salla Talvikki; Koivisto, Emilia; Korkka-Niemi, Kirsti; Rautio, Anne; Gee, Ryan (2021)
The Borehole Magnetic Resonance (BMR) method was tested for measuring porosity and estimating groundwater flow parameters required for hydrogeological modelling in a crystalline rock setting at the Sakatti Ni‐Cu‐PGE mining project site in Northern Finland. The characterization of hydraulic properties of deep bedrock, shallow fractured bedrock, surficial deposits as well as groundwater and surface water flow patterns and interactions between them is informative already during ore prospecting phase. Although BMR is widely used for determining storage and flow properties in sedimentary rocks forming hydrocarbon reservoirs, there have been few studies in basement rocks as described here. The BMR method allows the detection of water in the subsurface by applied electromagnetic fields in a continuous manner with decimetre‐scale measurements along the boreholes. The measured response is inverted to give a continuous distribution of relaxation time T2 which is a direct measure of the amount of water, or pore volume. This can further be divided into bound water and free water using specific cut‐off values for each lithology, which can then be used to calculate estimates of hydraulic conductivity. The Sakatti Cu‐Ni‐PGE deposit, located several hundred meters below the Natura2000‐protected Viiankiaapa mire, displays complex and heterogeneous subsurface geology, hydrogeology and deformational history. The BMR data was acquired from six drillholes in order to obtain specific information about the structural heterogeneity and free water content within the depth interval of 50 to 360m, and thus estimations of the local flow parameters. Other available survey data, such as natural gamma ray, acoustic image data, core logging and packer tests were compared with the BMR data in order to compare and calibrate the groundwater flow parameters calculated based on these measurements. The initial results indicate that BMR is a suitable tool for studying lithologically and hydrogeologically heterogeneous fractured crystalline rocks. ...